Interference of the blood clot on granulation tissue formation after tooth extraction. Histomorphological study in rats. - Okamoto, T.; Okamoto, Roberta [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP]; Gabrielli, M. F. (My University, 1994)
The interference of a blood clot in the first postoperative hours of dental extraction wounds was studied in rats. Sixty male albino rats were divided into two groups: Group I, immediately after extraction of right maxillary incisor the gingival mucosa was approximated and sutured; Group II, after 6 to 8 minutes postoperatively the blood clot was removed with saline irrigation and absorbent paper cones. The mucosa was then approximated and sutured. Six animals in each group were sacrificed after 12 hours, 1, 4, 7 and 10 days. There was a profound delay in healing in Group II since, although a new blood clot was later formed, it was not organized. The quality and the constitution, maintenance and retraction of the clot are the regulating factors in connective tissue formation during alveolar healing.
Keywords: animal; blood clotting; bone regeneration; granulation tissue; growth, development and aging; incisor; jaw; male; maxilla; physiology; rat; tooth extraction; Wistar rat; wound healing; Alveolar Process; Animals; Blood Coagulation; Bone Regeneration; Granulation Tissue; Incisor; Male; Maxilla; Rats; Rats, Wistar; Tooth Extraction; Wound Healing